ENHANCING USER EXPERIENCE (UX) IN BUS TICKET BOOKING: A CASE STUDY OF REDBus APPLICATION - Valencia Valencia; Lisana Lisana; Tyrza Adelia (LPPM Nusa Mandiri, 2024)
In Indonesia, the number of buses has increased significantly, particularly in major cities. Along with the advancement of mobile technology, people can now purchase bus tickets online using mobile applications. One of the popular online bus ticket booking platforms is RedBus. As one of the widely used applications, it is crucial to focus on User Experience (UX) because it significantly influences user satisfaction, encouraging continued use of the application. However, usability testing of the current RedBus application revealed that users are experiencing several issues, including difficulties in using the app, which leads to low user motivation and dissatisfaction with RedBus services. As a result, a redesign was needed to improve the UX of the RedBus application. Therefore, this study aims to investigate how UX can be improved after a redesign of the application. The redesign process employed the Design Thinking method, which consists of five phases: Empathize, Define, Ideate, Prototype, and Test. UX was measured through usability testing, focusing on effectiveness, efficiency, and user satisfaction. The measurement results of the redesigned RedBus application showed a 44% increase in effectiveness, with efficiency reaching 0.079 goals per second. Additionally, user satisfaction improved by approximately 63% across all criteria. These findings provide practical insights for designers and developers looking to enhance UX in their applications. They underscore the importance of a user-centered approach and demonstrate the effectiveness of Design Thinking as a framework for successful redesigns. Moreover, this research offers a practical guideline on how to measure UX for digital products